Magnetic Field-Assisted Photocatalytic Degradation of Organic Pollutants over Bi1−X Rx feo3 (R = Ce, Tb; X = 0.00, 0.05, 0.10 and 0.15) Nanostructures - Casagrande-Denardin, J; Radhalayam, D (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Magnetic-field-accelerated photocatalytic degradation of the phenol red (PR) as a model organic pollutant was studied using rare-earth elements modified BiFeO3 (Bi1−x Rx FeO3 (R = Ce, Tb; x = 0.0, 0.05, 0.10 and 0.15); BFO: RE) nanostructures. The nanostructures were prepared via the hydrothermal process and their morphological, structural, functional, optical and magnetic features were investigated in detail. The effect of magnetic fields (MFs) on photocatalysis were examined by applying the different MFs under visible light irradiation. The enhanced photodegradation efficiencies were achieved by increasing the MF up to 0.5T and reduced at 0.7T for the compositions x = 0.10 in both Ce and Tb substituted BFO. Further, mineralization efficiencies of PR, reproducibility of MF-assisted photocatalysis, stability and recyclability of BFO: RE nanostructures were also tested. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.